Study of prescription pattern of antihypertensives in diabetes with hypertension patients in geriatric population at tertiary care centre: a prospective observational study - Pal, Avinash D.; Baig, Mirza S.; Rao, Shailaja (International Journal of Research in Medical Sciences, 2025)
Background: Hypertension (HTN) and type 2 diabetes mellitus (T2DM) are prevalent chronic conditions that significantly affect elderly health, especially in India, where the dual occurrence of these diseases exacerbates cardiovascular risks. This study examines the prescription patterns of antihypertensive medications in geriatric patients with both conditions at a tertiary care center in Maharashtra, India. Methods: A prospective, cross-sectional study was conducted at government medical college, Aurangabad, from March 2023 to August 2024. Patients aged 60 and older with HTN and T2DM were included. Prescription data for antihypertensive medications were collected and analyzed. Results: The study included 1023 prescriptions, with 57.09% male patients. The most commonly prescribed antihypertensives were telmisartan (38.05%) and amlodipine (31.96%). Monotherapy was prescribed to 22.48% of patients, while 61.97% received two-drug combinations, and 14.66% received three-drug combinations. Only 0.88% of patients were prescribed more than three drugs. The most common combination therapy was Telmisartan and Amlodipine (59.78%). The majority of prescriptions were generic (91.18%), and 85.23% were from the national essential drug list (EDL) (India 2022), indicating cost-effective and standardized treatment practices. Conclusions: The study reveals a preference for ARBs and calcium channel blockers for managing HTN in elderly patients with T2DM. The widespread use of combination therapies and generic drugs reflects an efficient approach. Additionally, the study follows the WHO prescription parameters, with the average number of drugs per encounter being 1.93, and a high percentage of prescriptions aligning with EDLs.